2011
DOI: 10.1093/jb/mvr025
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of sams-1 and pmt-1 to lipid homoeostasis in adult Caenorhabditis elegans

Abstract: Accumulation of lipids inside the cell is primarily caused by disorders of lipid metabolism. S-adenosylmethionine synthetase (SAMS) produces SAM, an important methyl donor in various phospholipid methyltransferase reactions catalysed by phosphoethanolamine N-methyltransferase (PMT-1). A gel-based, quantitative proteomic analysis of the RNA interference (RNAi)-mediated inactivation of the pod-2 gene, which encodes acetyl-CoA carboxylase, showed a substantial down-regulation of SAMS-1. Consequently, RNAi of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 25 publications
3
53
0
Order By: Relevance
“…This was also found by two other groups (Li et al 2011;Walker et al 2011). Accordingly, depletion of the respective SAM-dependent phosphoethanolamine methyltransferases reduces PC levels in other organisms as well (Brendza et al 2007;Li et al 2011;Palavalli et al 2006).…”
Section: Sams-1 Regulates Homeostasis Between Phosphatidylcholine Andsupporting
confidence: 67%
See 2 more Smart Citations
“…This was also found by two other groups (Li et al 2011;Walker et al 2011). Accordingly, depletion of the respective SAM-dependent phosphoethanolamine methyltransferases reduces PC levels in other organisms as well (Brendza et al 2007;Li et al 2011;Palavalli et al 2006).…”
Section: Sams-1 Regulates Homeostasis Between Phosphatidylcholine Andsupporting
confidence: 67%
“…Asterisks indicate significant differences between WT worms and the respective sams-1 mutant at a given time point, determined using unpaired t tests with Welch's correction (*p \ 0.05; **p \ 0.01; ***p \ 0.001) larval stage to adulthood. Enlargement of LD in SAMS-1 deficient worms was recently described (Li et al 2011;Walker et al 2011). Worms passing through the L4 larvaeto-adult transition display dramatic germ cell proliferation, a marked extension of the gonadal arms, and gametogenesis, all of which are processes that consume large amounts of PC (Hubbard and Greenstein 2005).…”
Section: Sams-1 Links Phosphatidylcholine Synthesis To Lipid Droplet mentioning
confidence: 84%
See 1 more Smart Citation
“…This finding suggests that SAMS-1 and PMT-2 are not involved in sterol methylation because their levels were decreased in CS. It was also reported that SAMS-1 and PMT-1, another SAM-dependent methyltransferase, are down-regulated under stressful environmental condition and by pod-2 (acetylCoA carboxylase) RNAi (Li et al, 2011). Under these conditions, reduction of SAMS-1 and PMT-1 induced the accumulation of triacylglycerol lipid droplets in the intestine of worms (Li et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…It was also reported that SAMS-1 and PMT-1, another SAM-dependent methyltransferase, are down-regulated under stressful environmental condition and by pod-2 (acetylCoA carboxylase) RNAi (Li et al, 2011). Under these conditions, reduction of SAMS-1 and PMT-1 induced the accumulation of triacylglycerol lipid droplets in the intestine of worms (Li et al, 2011). Therefore, in CS condition, reduction of SAMS-1 and PMT-2 might also alter lipid metabolism and this change of lipid metabolism might affect larval development.…”
Section: Discussionmentioning
confidence: 96%